2013
DOI: 10.3109/02688697.2013.854313
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic work up for language testing in patients undergoing awake craniotomy for brain lesions in language areas

Abstract: Awake craniotomy is the technique of choice in patients with brain tumours adjacent to primary and accessory language areas (Broca's and Wernicke's areas). Language testing should be aimed to detect preoperative deficits, to promptly identify the occurrence of new intraoperative impairments and to establish the course of postoperative language status. Aim of this case series is to describe our experience with a dedicated language testing work up to evaluate patients with or at risk for language disturbances un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…The detailed screening, eligibility assessment and inclusion process is shown in Fig 1 . We included a total of forty-seven studies [ 10 , 17 62 ] in our SR. One author was personally contacted, and provided us more information about their used anaesthesia technique [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed screening, eligibility assessment and inclusion process is shown in Fig 1 . We included a total of forty-seven studies [ 10 , 17 62 ] in our SR. One author was personally contacted, and provided us more information about their used anaesthesia technique [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data of the study characteristics are shown in Table 1 . A total of fourteen case series [ 10 , 17 , 19 , 20 , 23 , 28 , 39 , 41 , 44 , 47 , 51 , 53 , 54 , 60 ] thirteen prospective studies [ 18 , 21 , 22 , 25 27 , 30 , 33 , 35 , 38 , 52 , 55 , 61 ], seventeen retrospective studies [ 24 , 29 , 31 , 34 , 37 , 40 , 42 , 43 , 45 , 46 , 48 50 , 57 59 , 62 ], two RCTs [ 32 , 56 ], and one pseudo-RCT [ 36 ] comprising 5945 AC procedures in 5931 patients were analysed ( Table 1 ). Of note, during the data extraction process it appeared that nine studies [ 20 , 22 , 27 , 31 , 42 46 ] partially repor...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because complications are common during awake craniotomy, prompt crisis management, team communication and experienced anesthetic and surgical teams are important to maximize the utility and safety of this procedure. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] Ethical disclosures…”
Section: Discussionmentioning
confidence: 99%
“…Un perfecto control de la anestesia y la realización meticulosa de los procedimientos de mapeo son esenciales para lograr la mayor precisión con los resultados de la localización cerebral. Por último, puesto que es común que se presenten complicaciones durante la craneotomía en el paciente despierto, la comunicación y un equipo integrado por cirujanos y anestesiólogos expertos son importantes para maximizar la utilidad y la seguridad de este procedimiento [27][28][29][30][31][32][33][34][35][36][37][38][39][40] .…”
Section: Conclusionesunclassified